Managing knock your socks off service - Bell, Chip R. (AMACOM, 2007)
In today's high-speed economy, the organizations that come out on top are those that service customers best. Serve customers ""about as good as anybody else"" and you wont be serving them for long! Serve them with distinction, and they will be customers for life. Today's customer demands service that is above the norm ... service that makes its mark in their minds and hearts. The 2nd edition of ""Managing Knock Your Socks Off Service"" has been revamped with new examples, new stories, new research and new chapters to share with readers how they can successfully create world-class service in the